Extrinsic compression of pancreactic duct by intragastric balloon treatment and its potential to cause acute pancreatitis: two case reports and clinical discussion. Issue 2 (March 2020) - Halpern, Bruno; Paulin Sorbello, Mauricio; Telles Libanori, Hilton; Correa Mancini, Marcio
Abstract: We describe two cases of increased pancreatic enzyme levels after intragastric balloon (IGB) placement possibly related to extrinsic pancreatic duct compression, followed by a short review of the literature. Case 1 is the first, to our knowledge, of a patient with asymptomatic increase of pancreatic enzymes due to pancreatic duct compression, with unknown clinical significance. We hypothesize that this finding maybe can be relatively common in IGB users and almost certainly an important risk factor for the development of acute pancreatitis (AP). On the other hand, case 2 reports an AP that occurred one day after IGB placement, presented with nausea and vomiting, making AP a differential diagnosis of initial IGB intolerance.